The novel therapy of brain tumors - Rolle, Katarzyna; Nowak, Stanisław; Wyszko, Eliza; Piwecka, Monika; Żukiel, Ryszard; Barciszewska, Mirosława Z.; Barciszewski, Jan (Przewodnik Lekarza/Guide for GPs, 2011)
Malignant gliomas show uncontrolled proliferation, invasiveness, limited proliferation and dynamic angiogenesis. Despite the treatment of gliomas with surgery, radiation and chemotherapy only short prolongation of the live is achived. Brain tumor cells express preferentially a number of proteins that play a crucial role in tumorigenesis, being a good potential therapeutic target, such as tenascin-C. We discovered a novel strategy based on RNA interference (RNAi) what leads to inhibition of tenascin C synthesis. We implemented this therapy as experimental treatment in Department of Neurosurgery and Neurotraumatology University of Medical Sciences in Poznan. We show therefore that this therapy improves overall survival and quality of life.